Bio-Physics Concept For Camera Vision Hypothesis Of Colour White - Zakaria, Shahrudin; Syed Salim, Syed Najib; Che Hasan, Mohd Hanif; Zainon, Maslan; Abd Razak, Norazlina (Research India Publications, 2017)
In the myriad of colours, black and white are strange colours to be discussed. Since black (the colour that one perceives) is not in the Electromagnetic (EM) spectrum, it is duly suggested that black is an interpretation of the brain in which the existing “no signal” concept is also discussed in the article. The same goes to the colour white, it is not in the EM spectrum too, so it is also duly proposed as an interpretation of the brain. The concept of white as combination of colour is also discussed in the article. It is insignificant to discuss about both these colours of their existence in the reflection of colour representation since their non-existent in EM spectrum is similar to the colour pink or magenta. There is a hypothesis (for white light colour theory test) at the end of this article, the authors welcome any scientists or engineers or researcher all over the world to assess, deliberate and prove the truth of this theory.